PELAKSANAAN PEMBELAJARAN DARING PADA MATA PELAJARAN GEOGRAFI KELAS XI IPS SMA SANTUN UNTAN PONTIANAK - Trisna Wati Nome; Sri Buwono; Putri Tipa Anasi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study has a purpose, namely to find out the implementation of online learning on geography subjects in class XI IPS and student learning outcomes. This research is a type of descriptive research with a form of qualitative research. The data sources for this study were the teacher of geography and the students of class XI IPS. Data collection techniques are interviews and documentation. The results of this study are (1) the implementation of online learning on geography subjects in class XI IPS consists of: (a) learning materials: the teacher delivers material using google classroom, (b) learning media: the media used are pictures and videos, (c) ) teaching strategy: the teacher provides material in the form of videos and explanations, provides motivation to keep the spirit in learning, (d) constraints: there are students who do not have cellphones/laptops, do not have sufficient internet quota, unstable internet network, do not collect assignments on time, (e) advantages: can learn anywhere and anytime, cost-effective, and makes it easier for students to learn independently, (f) disadvantages: must have sufficient internet quota, the network is not good and students also do not understand the material being taught. convey through google classroom (2) Student learning outcomes, from 25 students who managed to achieve the KKM score only 8 people (32%). So, for student learning outcomes in online learning, Indonesian natural resource materials cannot be said to have succeeded in reaching the KKM.Keyword: implementation, learning outcomes, online learning